RESEARCH OF CHARACTERISTICS OF WEIGHTS - ANALYZERS WITH THREE-DIMENSIONAL MONOPOLAR HF FIELDS WITH SQUARE-LAW DISTRIBUTION OF POTENTIAL - Hizirova, M.A.; Аhmediyarova А.Т.; Kasimova D.Т.; Nurtaeva G.К. (Recent Contributions to Physics, 2018)
Experimental mass analyzers from two are investigated and three-dimensional linear monopolar high-frequency fields, define their analytical possibilities and consumer characteristics.